Farmers’ Perception about the Use of Sorghum (Sorghum bicolor (L.) Moench) Landraces and Their Genetic Erosion in South Wollo Administrative Zone, Ethiopia - Silamlak Birhanu Abegaz; Faris Hailu Tessema (International Journal of Agronomy)
Genetic erosion can result in the loss of sorghum landrace genetic diversity. In the study areas, although it is generally believed that genetic erosion had occurred, there are no data on its amount and extent. Thus, this study is aimed to assess farmers’ perception about the use of sorghum landraces and their genetic erosion and to identify suggested reasons for the replacement of sorghum landraces. To this end, a field survey of 1200 farmers, randomly selected over the three districts (Tenta, Mekdela, and Delanta) during 2006 to 2015/2016 main cropping seasons, was undertaken. Structured questionnaire survey of households, focused group discussions, key informant interviews, and field observations were used to collect data. Moreover, the data for samples collected during 1980 were obtained from the Ethiopian Biodiversity Institute (EBI). Sorghum landrace history profile analysis indicated that there was an insight in the use of local varieties among local farmers over the past three or above decades. However, there is a reduction trend due to the different selection criteria described by farmers. “Kokita,” “Merar,” “Marchuke,” “Tinkish” (except for “Necho-Tinkish” and “Jofa-Tinkish”), and “Fesho” were totally excluded (lost) by local farmers attributed by home consumption preferences. The interviewed farmers indicated that genetic erosion had occurred. Genetic erosion of 100% was observed in white sorghum in Mekdela and 66.7% in Delanta and Tenta districts. Likewise, genetic erosion of red sorghum, 25%, 20%, and 75%, respectively, was detected in Tenta, Mekdela, and Delanta. For yellow sorghum grains, genetic erosion was 33.4% in Tenta and 66.7% in Mekdela and Delanta. Genetic erosion for “Tinkish” was found to be 66.7% in Tenta and 50% in Mekdela and Delanta. Based on farmer responses, genetic erosion was attributed to reduced benefits from landraces, drought, climate change, market price and demand, and reduction in land size. The actions of both natural and conscious selection on farm were also discussed in detail as genetic erosion scenarios. Therefore, attention should be given to conservation of farmers’ varieties in which involving farmers’ participation is very important in order to use their indigenous knowledge for conservation of FVs and on-farm conservation strategies should be practiced for FV sustainable use. Thus, genetic resource conservation is attained.